Reflections on peer micro-teaching: raising questions about theory informed practice. Issue 3 (4th May 2021) - Crichton, Hazel; Valdera Gil, Francisco; Hadfield, Christine
ABSTRACT: This paper considers student teachers as reflective practitioners arguing that reflection processes can be established in university pre-service programmes, rather than the more widely acknowledged school practicum. Results from a small-scale study into micro-teaching sessions, where student teachers taught peers, indicate that 'teachers' and 'learners' benefitted from sharing knowledge, and from reflection afterwards, evaluating teaching and learning approaches and considering strategies for future practice. Increased confidence, teamwork and appreciation of practical considerations: organisation, planning and resources were all highlighted by students after the sessions. We conclude that stimulating reflection in the university setting through peer teaching offers a helpful perspective for teacher educators, so that during school practicum, students can interrogate their practice effectively, enhancing their pedagogy. We also raise questions about theory-informed practice and its role in reflection.